Trace Metal Detection in Aqueous Reservoirs Using Stilbene Intercalated Layered Rare-Earth Hydroxide Tablets - Solomon Omwoma (Journal of Analytical Methods in Chemistry)
Contamination of aquatic reservoirs with metal ions is a slow gradual process that is not easy to detect. Consequences of the metal ions, especially the ones with high atomic numbers (heavy metals) at high concentrations, are severe and irreversible in aquatic reservoirs. As such, early detection mechanisms, especially at trace concentration, are essential for mitigation measures. In this work, a new, robust, and effective tool for trace metal detection and monitoring in aqueous solutions has been developed. Tablets (1 mm thick and similar to medicinal tablets) were manufactured from a powder comprising stilbene intercalated into gallery spaces of lanthanide-containing layered double hydroxides. The tablets were placed in a water column having different concentrations of Pb2+ and Cu2+ ions, and the water was allowed to flow for 45 minutes at a flow rate of 100 ml/s. Thereafter, the tablets were dried and made to powder, and their phosphorescence was measured. The gradual stilbene phosphorescence turnoff in the tablets from various concentrations of metal ions was correlated with sorption amounts. The tablets were able to detect effectively metal ions (up to Pb2+ 1.0 mmol/L and Cu2+ 5.0 mmol/L) in the aqueous media. As such, the concentrations of Pb2+ and Cu2+ ions at trace levels were determined in the test solutions. This method provides a real-time metal ion analysis and does not involve sampling of water samples for analysis in the laboratory.